99mTc‐Ceftizoxime: Synthesis, characterization and its use in diagnosis of diabetic foot osteomyelitis. Issue 1 (10th December 2018) - Ahmed, Naseer; Fatima, Shazia; Saeed, Muhammad Adnan; Zia, Muhammad; Irfan Ullah, Javaid
Abstract: Introduction: The diagnosis of diabetic foot osteomyelitis is crucial and challenging for the proper management of diabetic foot. 99m Tc labelled Ceftizoxime was used as a non‐invasive diagnostic agent for diabetic foot osteomyelitis. Methods: Ceftizoxime [CFT], a third generation cephalosporin, was used in a simple and direct method for the synthesis of 99m TcO4 − labelled infection imaging agent with stannous chloride as reducing agent. Its radiochemical purity was checked by thin Layer chromatography. Partition co‐efficient was measured with phosphate buffer and chloroform. The radiochemical complex was injected to control and infected animal model for 3 hours in‐vivo localization studied with the help of dual head gamma camera. The labelled complexes were injected to 5 patients of known type II diabetes mellitus suspected of diabetic foot osteomyelitis. All patients underwent dynamic and static 99m Tc‐MDP and 99m Tc‐CFT scans. Results: The synthesized radio labelled complex was 98.8% pure, with hydrophilic character. When injected to animal model, at 120 minutes, 49.3% was localized in foci of infection with 3.35% in liver and excretion through kidney. Human studies were interpreted as true or false positive and true or false negative based on bone histopathology/culture and clinical follow‐up. We found that of 5 patients, 2 were true positive, 2 as true negative with no false positive or negative and 01 patient had soft tissue infection. Conclusion: This study showed that 99m Tc‐CFT labelled complex could be used for detection of diabetic foot osteomyelitis; however, further confirmation of results with a larger patient population would be optimal.